2003
DOI: 10.1103/physrevb.67.054502
|View full text |Cite
|
Sign up to set email alerts
|

Phase-slip-like resistivity in underdopedYBa2Cu3O7

Abstract: We investigated the anomalous peak resistivity below the onset T c in underdoped YBCO, reminiscent of that observed in 1D wires of conventional superconductors. We performed measurements of the angular dependence of resistivity ρ(θ) in a magnetic field and the temperature dependence of resistivity ρ(T ), which exhibit a peak for B ab-planes. This peak in ρ(T ) disappears for B c-axis. The width of the corresponding maximum in ρ(θ) at θ = 0 o (B ab-planes) decreases with increasing c-axis component of the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Phase slips and the flow of current in filaments has also previously been proposed to explain resistivity close to T c in unpatterned YBa 2 Cu 3 O 7 ͑YBCO͒ films. 19,20 At currents above the critical current I c , current-driven phase slip centers ͑PSCs͒ have also been observed in both low-temperature superconductors 21 and high-temperature superconductors. 22,23 These manifest themselves as a series of rather regular voltage steps in the I͑V͒ characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Phase slips and the flow of current in filaments has also previously been proposed to explain resistivity close to T c in unpatterned YBa 2 Cu 3 O 7 ͑YBCO͒ films. 19,20 At currents above the critical current I c , current-driven phase slip centers ͑PSCs͒ have also been observed in both low-temperature superconductors 21 and high-temperature superconductors. 22,23 These manifest themselves as a series of rather regular voltage steps in the I͑V͒ characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillation phenomena on the R-T curves was observed, which was in the range from the superconductor transition temperature (T C ) to the pseudopotential temperature. The further study by Abdelhadi et al [9] revealed that this physical phenomenon was induced by the Phase Slip. The I V curves of the microbridge structures fabricated by Morales et al [10] show S figures, which is consistent with the superconductive phase slippage theory.…”
mentioning
confidence: 96%
“…Highly non-linear I-V characteristics and anomalous resistance versus temperature behavior have been attributed to either collective flux-flow, phase slips or mesoscopic domains [19,20,21,22,23]. The V -I characteristics of YBCO microstrips fabricated using our technique are shown in Figure 2.…”
mentioning
confidence: 99%